2011
DOI: 10.1111/j.1365-2958.2011.07843.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis virulence regulator AtxA: oligomeric state, function and CO2‐signalling

Abstract: Summary AtxA, a unique regulatory protein of unknown molecular function, positively controls expression of the major virulence genes of Bacillus anthracis. The 475-amino acid sequence of AtxA reveals DNA-binding motifs and regions similar to proteins associated with the phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS). We used strains producing native and functional epitope-tagged AtxA proteins to examine protein-protein interactions in cell lysates and in solutions of purified protein. Co-affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(101 citation statements)
references
References 65 publications
(102 reference statements)
2
99
0
Order By: Relevance
“…These results suggest that the expression and function of the trans-acting repressor protein(s) is not impacted by the CO 2 /bicarbonate signal. Notably, previous reports indicated that the CO 2 /bicarbonate signal enhances toxin and capsule gene expression by affecting AtxA protein function, rather than atxA expression (10,13,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggest that the expression and function of the trans-acting repressor protein(s) is not impacted by the CO 2 /bicarbonate signal. Notably, previous reports indicated that the CO 2 /bicarbonate signal enhances toxin and capsule gene expression by affecting AtxA protein function, rather than atxA expression (10,13,24).…”
Section: Discussionmentioning
confidence: 99%
“…An isogenic ANR-1 atxA-null mutant (UT374) was created using pUTE937 and the markerless temperature-sensitive integration system previously described by Pflughoeft et al (37). Detailed explanation of pUTE937 construction can be found in the study reported by Hammerstrom et al (24). Similar methods were used to create the isogenic ANR-1 atxA-up mutant (UT398).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenicity of Bacillus anthracis is governed by two large extrachromosomal plasmids namely pXO1 and pXO2. The plasmid pXO1 encodes protective antigen, lethal factor, edema factor and anthrax toxin activator A (AtxA), a central regulator for toxin synthesis [41]. These secreted toxin units enable the pathogen to establish a systemic infection in short duration of time.…”
Section: Bacillus Anthracismentioning
confidence: 99%